A review of the empirical research on export channel selection between 1979 and 2015. Issue 2 (April 2017) - Li, Min; He, Xinming; Sousa, Carlos M.P.
Highlights: We review the export channel selection empirical studies. We analyse determinants and the consequence of export channel selection. Areas to be strengthened include theoretical basis and methodological issues. We provide suggestions for future research. Abstract: Export channel selection is an important strategy for exporting firms. Over the last 45 years, there have been a number of studies investigating the antecedents and outcomes of this strategy. However, no single study systematically reviews the findings in this field. In order to address this gap, we review the literature on export channel selection up to 2015 and analyse findings on the determinants and/or consequences of export channel selection. Our review shows that in general export channel selection remains underexplored. We identify a number of issues in the current studies, including lacking knowledge of performance implication of channel selection, missing theoretical bases, weaknesses of research methods. Based on these, this review provides future research directions for development in export channel selection research.